The role of filler-epoxy interface and traps in the dielectric breakdown performance in epoxy moulding compounds (EMC) - Chua, Lin Xiao (Nanyang Technological University, 2023)
With the increasing popularity of electric vehicles (EV) due to the need to reduce carbon dioxide (CO2) emissions, the demand for better and more cost-efficient power electronics continues to increase. In order to improve the efficiency and effectiveness of these power electronics, the requirements for these power electronics to operate at higher voltages, frequencies, and temperatures began to increase. However, the challenges and associated problems to meet these demands also correspondingly increase. One of such problems is the higher failure rate of the electronic packaging materials of the power devices at higher voltages and frequencies, and the lack of understanding on its failure mechanism. The focus of this study is on the understanding on how high voltage and high frequency will affect the dielectric breakdown of Epoxy Moulding Compound (EMC), that is used as the packaging material in power electronics, and the role of filler-polymer interface and traps on the dielectric breakdown mechanism. The methodology adopted in this study mainly focuses on how filler treatment will affect the dielectric breakdown mechanism of the EMC. Specifically, the interfacial properties, trap properties and AC dielectric breakdown strength of EMC formulations were studied. Aminosilane (AS), Epoxysilane (ES) and Mercaptosilane (MS) were used to modify the treated fillers in EMC formulations to induce differences in the interfacial region. The changes in the interfacial properties due to the type and amount of coupling agents were characterised using Fourier-Transform Infrared (FTIR) Spectroscopy, Dielectric Spectroscopy and Scanning Electron Microscopy (SEM). These characterisations were used to explore any correlations between the EMCs structural properties and deep trap properties, which was measured using Thermally Stimulated Depolarisation Current (TSDC) test system, and AC dielectric breakdown strength, which was measured using High Voltage (HV) AC tester. This thesis found that the improvement in filler dispersion (from the reduction in filler aggregation rate and filler size distribution) correlate with an increase in the AC dielectric breakdown strength. The increase in deep trap depth and density was also found to correlate with an increase in the AC dielectric breakdown strength. The changes in trap properties, due to the addition of coupling agents, can be explained by the Maxwell-Wagner-Sillars (MWS) polarisation and the β-relaxation mechanisms. EMC with 100% AS-treated silica was measured to have the highest dielectric breakdown strength of 21.41 ± 0.20 kV/mm. From these results, the correlation between the different properties studied were established to bring about a better understanding on the role of the filler-epoxy interface and traps on the dielectric breakdown performance of EMCs for power electronics packaging.